2017
DOI: 10.3856/vol45-issue3-fulltext-8
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of the green turtle Chelonia mydas in northern Peru

Abstract: ABSTRACT. Diet and food preferences of the green turtle Chelonia mydas were analyzed based on digestive tract contents of dead specimens caught incidentally by an artisanal gillnet fishery in Sechura Bay, northern Peru. We examined 27 digestive tracts and identified 35 prey items. The sampled turtles were all juveniles (CCL = 53.7 ± 1.2 cm, range 40.5-67.0 cm). The prey items were grouped into six categories: algae, cnidarians, mollusks, arthropods, chordates and garbage/anthropogenic debris. The items with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Animal matter. Animal matter featured to some degree in all sub-regions, especially the following: Pacific S Central pelagic sites (mean = 35%; SE = 35; n = 2; e.g., Piovano et al 2020); Pacific E neritic sites (mean = 30.9%; SE = 7.2; n = 18; e.g., Amorocho and Reina 2007;Jiménez et al 2017;Quiñones et al 2010; Paredes 2015); Mediterranean neritic sites (mean = 31.9%; SE = 19.7; n = 5; e.g., Lazar et al 2010;Karaa et al 2012); Indian SE neritic sites (mean = 20.7%; SE = 9.3; n = 5; e.g., Burkholder et al 2011;Thomson et al 2018); and at Atlantic E upwelling sites (mean = 25%; SE = 5; n = 2; e.g., Hancock et al 2018).…”
Section: Global Review Of Green Turtle Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal matter. Animal matter featured to some degree in all sub-regions, especially the following: Pacific S Central pelagic sites (mean = 35%; SE = 35; n = 2; e.g., Piovano et al 2020); Pacific E neritic sites (mean = 30.9%; SE = 7.2; n = 18; e.g., Amorocho and Reina 2007;Jiménez et al 2017;Quiñones et al 2010; Paredes 2015); Mediterranean neritic sites (mean = 31.9%; SE = 19.7; n = 5; e.g., Lazar et al 2010;Karaa et al 2012); Indian SE neritic sites (mean = 20.7%; SE = 9.3; n = 5; e.g., Burkholder et al 2011;Thomson et al 2018); and at Atlantic E upwelling sites (mean = 25%; SE = 5; n = 2; e.g., Hancock et al 2018).…”
Section: Global Review Of Green Turtle Dietmentioning
confidence: 99%
“…We conclude that green turtle omnivory may be partly driven by water temperature, and we present the first quantitative evidence that temperature may be an important driver of diet in green turtles at a global scale, especially where the diet includes gelatinous macrozooplankton (in particular, jellyfish and salps). Gelatinous macrozooplankton featured most prominently at oceanic and extreme-latitude sites in the Pacific and Atlantic, ranging from 40% in the Pacific NW (Fukuoka et al 2016); 30-73% in the oceanic Pacific NC (Parker et al 2011;Wedemeyer-Strombel et al 2015); 38-72% along the Pacific E coastline (Seminoff et al 2006;Amorocho and Reina 2007;Quiñones et al 2010;Lemons et al 2011;Jiménez et al 2017); and 40-59% in the Atlantic SW (Bugoni et al 2003;González Carman et al 2014). A feature shared by all these sites appears to be much cooler water temperatures (< 20 °C) during all or part of the year.…”
Section: Sst As a Driver Of Variation In Green Turtle Dietmentioning
confidence: 99%
“…Eretmochelys imbricata, and Lepidochelys olivacea); all are listed from vulnerable to critically endangered on the IUCN Red List (IUCN, 2018) and have documented interactions with marine litter. The green turtle (C. mydas) is the species most commonly mentioned to have ingested plastic items, with a frequency ranging from 28% in the Ecuadorian part of the HCS (Alemán, 2014) to 56 and 91% in Peru (Alfaro-Shigueto et al, 2005;Jiménez et al, 2017). The olive ridley turtle (L. olivacea) also has a high incidence of plastic ingestion, reaching up to 43% in Ecuador (Alemán, 2014), but this species has a lower incidence in other parts of the HCS (8%), both in Peru and southern Chile (de Paz et al, 2005;Brito et al, 2007).…”
Section: Sea Turtlesmentioning
confidence: 99%
“…Items most commonly found in stomachs or intestines of sea turtles are plastic pieces of intermediate size, including plastic bags, monofilament nylon, rope, and fishing nets (Brito, 2001;Guerra-Correa et al, 2007;IMARPE, 2011;Jiménez et al, 2017; Figure 3C). Several authors suggested that plastic ingestion has been the cause of death of stranded turtles in Ecuador and Chile (Brito et al, 2007;Silva et al, 2007;Alemán, 2014).…”
Section: Sea Turtlesmentioning
confidence: 99%
“…Caulerpa filiformis is a green alga found in South Africa, Mozambique, Peru and Australia [38][39][40][41]. On the east coast of Australia, C. filiformis has become locally abundant on temperate shallow rocky reefs well outside its historic distribution [40][41][42]. These range expansions have negative effects on co-occurring macrophytes [43] representing a similar invasive behaviour as Caulerpa taxifolia and Caulerpa racemosa in southeastern Australia, the Mediterranean and United States [44,45].…”
Section: Introductionmentioning
confidence: 99%